2018
DOI: 10.3390/cancers10010018
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Pathways in Cancer and Autophagy

Abstract: TOR (target of rapamycin), an evolutionarily-conserved serine/threonine kinase, acts as a central regulator of cell growth, proliferation and survival in response to nutritional status, growth factor, and stress signals. It plays a crucial role in coordinating the balance between cell growth and cell death, depending on cellular conditions and needs. As such, TOR has been identified as a key modulator of autophagy for more than a decade, and several deregulations of this pathway have been implicated in a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
226
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(235 citation statements)
references
References 156 publications
(189 reference statements)
6
226
0
3
Order By: Relevance
“…Our studies revealed inhibition of mTOR and its activity in both mouse models of ALD and in humans. Inhibition of mTOR activity was shown to increase autophagy . We found disruption of autophagy at the lysosomal level.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Our studies revealed inhibition of mTOR and its activity in both mouse models of ALD and in humans. Inhibition of mTOR activity was shown to increase autophagy . We found disruption of autophagy at the lysosomal level.…”
Section: Discussionmentioning
confidence: 61%
“…We found disruption of autophagy at the lysosomal level. Apart from its role in autophagy, mTOR is a central regulator of cell growth, proliferation, and survival in response to nutritional status, growth factor, and stress signals . A recent study showed a role of mTOR in the regulation of exosome release.…”
Section: Discussionmentioning
confidence: 99%
“…Because the mTOR signaling pathway plays a vital role in the process of autophagy, it is important to study the relationship between the mTOR pathway and autophagy. The mTOR includes 2 functionally and biochemically distinct complexes, mTORC1 and mTORC2 . Evidence has shown that mTORC1, but not mTORC2, plays a vital role in the regulation of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is regulated by a complex signaling network and mTOR pathway is the main regulatory mechanism for its suppression (Paquette et al, 2018[20]). We observed that exenatide was able to inhibit insulin stimulatory effect in a more significant way than liraglutide, proving to have a greater effect.…”
Section: Discussionmentioning
confidence: 99%